Aplicação mecanizada de N-P-K individualizada na cultura da cana-de-açúcar - Carneiro, Franciele Morlin [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Brazil is the largest producer of sugarcane, due to expansion of cultivated areas, mechanized fertilizer becomes very important for the increase in operating performance in this culture, but this fertilization may show some problems in the distribution of fertilizers, so that when not performing the characterization of fertilizers through the angle of repose, particle size and density of nutrients, among other. Thus, it becomes necessary to develop new technologies that enable an improvement in the application of fertilizers in the cultivation of sugarcane. In view of this, a new concept of fertilizer in development considered as a prototype because this performs individualized application of nitrogen, phosphorus and potassium, providing greater efficiency in the distribution of these over other fertilizer machine. With this work the objective was to evaluate the mechanical application of NPK individualized culture of sugarcane. The experiment was conducted in the Matão municipality in the area of sugarcane belonging to the Fazenda Cascavel, possessing approximately 1.66 ha experimental area. The experimental design was completely randomized (DIC), with three treatments and thirty replications for treatment. This design was established according to the criteria of quality control, and monitoring of variables held during fertilization operation. At the end of the evaluation period were collected 90 sample points in total, with 30 points per treatment. The treatments were: 1- mechanized fertilized, without herbicide; 2- Operation combined (simultaneous application of herbicide and fertilizer); and 3- Two operations (separate application of herbicide and fertilizer). It was concluded that the best operational quality through control charts was the third treatment, two operations (separate application of herbicide and fertilizer) for presenting less variability. The right side of fertilizer machine was the best for having applied ...

O Brasil é o maior produtor mundial de cana-de-açúcar, devido a expansão de áreas cultivadas, a adubação mecanizada torna-se muito importante para o aumento do desempenho operacional nesta cultura, porém esta adubação pode demonstrar alguns problemas na distribuição de fertilizantes, como a não realização da caracterização dos fertilizantes por meio do ângulo de repouso, granulometria e densidade dos nutrientes, entre outros. Dessa forma, torna-se necessário o desenvolvimento de novas tecnologias que possibilitem uma melhora na aplicação de fertilizantes na cultura da cana-de-açúcar. À vista disso, um novo conceito de adubadora está em desenvolvimento considerada como protótipo, pois esta realiza aplicação individualizada de nitrogênio, fósforo e potássio proporcionando maior eficiência na distribuição destes em relação às outras adubadoras. Com este trabalho o objetivo foi avaliar aplicação mecanizada de N-P-K individualizada na cultura da cana-de-açúcar. O experimento foi desenvolvido no município de Matão em área de cana-de-açúcar pertencente à Fazenda Cascavel, possuindo 1,66 ha aproximadamente de área experimental. O delineamento experimental foi Inteiramente Casualizado (DIC), com três tratamentos e trinta repetições por tratamento. Este delineamento foi estabelecido conforme os critérios do controle de qualidade, sendo o monitoramento das variáveis realizado durante a operação de adubação. Ao final do período de avaliação foram coletados 90 pontos amostrais no total, sendo 30 pontos por tratamento. Os tratamentos foram: 1- Adubação mecanizada, sem aplicação de herbicida; 2- Operação conjugada (aplicação simultânea de herbicida e adubação); e 3- Duas operações (aplicação separada de herbicida e adubo). Concluiu-se que a melhor qualidade operacional por meio das cartas de controle foi o tratamento 3, sendo duas operações (aplicação separada de herbicida e adubo)...
Keywords: Controle de processo - Métodos estatísticos; Cana-de-açúcar; Adubos e fertilizantes; Máquinas agrícolas; Adubação; Process control Statistical methods